2019
DOI: 10.1111/sms.13556
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of laboratory‐based methods to calculate jump height and improvements to the field‐based flight‐time method

Abstract: Laboratory methods that are required to calculate highly precise jump heights during experimental research have never been sufficiently compared and examined. Our first aim was to compare jumping outcome measures of the same jump, using four different methods (double integration from force plate data, rigid‐body modeling from motion capture data, marker‐based video tracking, and a hybrid method), separately for countermovement and squat jumps. Additionally, laboratory methods are often unsuitable for field use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…The flight time method calculates force and velocity based on jump height [15]. However, flight times are inevitably prone to small errors in technical execution [49], in addition to systematic errors compared to jump height obtained from force data [50,51]. As Jime ´nez-Reyes et al [15] point out, the FV-variables are associated with cumulative extrapolation errors, consecutively decreasing the validity of these variables.…”
Section: Agreement Among Methodsmentioning
confidence: 99%
“…The flight time method calculates force and velocity based on jump height [15]. However, flight times are inevitably prone to small errors in technical execution [49], in addition to systematic errors compared to jump height obtained from force data [50,51]. As Jime ´nez-Reyes et al [15] point out, the FV-variables are associated with cumulative extrapolation errors, consecutively decreasing the validity of these variables.…”
Section: Agreement Among Methodsmentioning
confidence: 99%
“…This method does not account for the center-of-mass displacement before take-off, and thus underestimates jump height. However, this method remains appropriate to estimate flight distance ( Wade et al, 2020 ), especially outside laboratory conditions, and we observed low variability within-participants. Recent field-based estimates of jump height appear to be an interesting alternative of the use of the flight time method by adding the calculation of an anatomically scaled heel-lift constant to improve jump height estimation ( Wade et al, 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…However, this method remains appropriate to estimate flight distance ( Wade et al, 2020 ), especially outside laboratory conditions, and we observed low variability within-participants. Recent field-based estimates of jump height appear to be an interesting alternative of the use of the flight time method by adding the calculation of an anatomically scaled heel-lift constant to improve jump height estimation ( Wade et al, 2020 ). Lastly, considering the unequal samples for fascicle related data ( N = 12) and EMG data ( N = 10 and 8 for GM and VL, respectively), caution should be made when interpreting these variables together.…”
Section: Discussionmentioning
confidence: 89%
“…Both the signal acquired from the FP and the signal acquired from IMU were filtered using a low-pass Butterworth filter (order = 5, f cof = 40 Hz). The calculation of the jump height from IMU data was performed using the FT method [13,22,27] by Equation (1).…”
Section: Measurement Equipmentmentioning
confidence: 99%
“…The vertical jump (VJ) is a complex task that requires the coordination of multiple joints [1]. It is characterized by a rapid vertical acceleration of the body mass in the shortest possible time interval and was found to be related to common sports activities, such as sprint, acceleration and change of direction speed (CODS) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%